A fluid dynamic analysis of the propulsive of the hand and forearm in swimming - Wood, T. C. (Swimming III. Proceedings of the Third International Symposium of Biomechanics in Swimming, University of Alberta, Edmonton, Canada, 1979)
For many years a predominant theory in swimming has been than momentum is achieved by the form drag force created by the hand (Counsilman, 1968), ana swimmers have been advised to pull in a straight line, horizontally directly backward. Recently, however, observations of skilled swimmers by film analysis (Counsilman, 1969; Barthels and Adrian, 1975) have shown that this does not occur. Deviating limb tracks in the alternating swimming strokes are clearly associated with movements counteractive to rotational forces generated elsewhere in the body and in the symmetrical strokes with anatomic andphysiological considerations (Wood, 1978). It has been suggested that in following such deviating pathways the hand behaves as a fluid foil, creating forces of lift that act perpendicular to the direction of movement of the foil or hand. It has been suggested further that these lift forces, rather than form drag forces that operate in the opposite direction to the line of motion of the hand, are the main propulsive forces generated by the hands in swimming (Counsilman, 1969; Schleihauf, 1974). This study arose out of this "lift versus drag" controversy and was designed to examine the fluid foil characteristics of the hand and forearm (Wood, 1977) in model form, in a controlled and measurable situation, to determine the nature and magnitude of the forces that the upper limb can generate.